CLINICAL AND INSTRUMENTAL CHARACTERISTICS OF JUVENILE CHRONIC ARTHRITIS EVOLUTION - Lebets, I. S.; Zaytseva, E. M.; Letyago, G. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
The purpose of the study was to investigate the clinical symptoms and evolution of juvenile chronic arthritis (JCA) at different stages of it development. 39 children with duration of JCA from 6 months to 5 years in age from 2 to 18 years were examined. All patients underwent clinical examination, indicators of acute phase of inflammation (CRP, sialic acid, seromucoid, glycoproteins), rheumatoid factor, circulating immune complexes, complement, instrumental methods (X-ray and ultrasound, capillaroscopy of nail bed) were evaluated. Activity of the disease was estimated by disease activity score (DAS28). Statistically was determined the relative value (P). It was found that the disease started with monoarthritis (63,37 %). In the future, in half of the patients was formed oligoarthritis with damaging of large and medium-sized joints (68,25 %). In the majority of surveyed disease occurred against the backdrop of the minimal activity of the inflammatory process. On the stages of evolution recurrence of arthritis were observed in one third of children. If duration of the sickness is more than 5 years, it has become less frequent, than in previous years. The absence of clinical and radiographic manifestations of JCA after the abolition of medical treatment within one year, became the basis for the assumption that the disease remission, which was on the third year of the disease 25,93 %, on the fourth – 33,33 %, on the fifth – 36,36 %. The absence of radiographic signs of bone destruction, disability of patients allows interpreting JCA as a positive option of chronic juvenile idiopathic arthritis.